2022
DOI: 10.5194/aab-65-449-2022
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of prolactin (PRL) gene exon 5 and its association with egg production in IPB-D1 chickens

Abstract: Abstract. The prolactin (PRL) gene regulates the egg production and incubation in laying chickens. Local chickens' reproductive systems will disrupt as a result of the incubation period activity, and they will lay fewer eggs. This study aimed to determine the prolactin gene polymorphism in IPB-D1 hens and its relationship to egg production. The polymorphism of the exon 5 prolactin gene was examined on 112 samples of the IPB-D1 chicken DNA collection from the Division of Animal Genetics and Breeding, Faculty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Investigated from five native duck breeds (Shanma, Shaoxing, Jinyun, Jingjiang and Youxian), Wang et al (2011) reported that polymorphism at PRL/PstI in exon 5 was detected, and ducks bearing CC genotype possessed higher egg production as well as egg weight than those of the CT genotype. Similar results of polymorphism at the PRL/ PstI locus in different duck breeds and its relationship with reproductive traits such as egg production ability was also reported in other studies in ducks (Ghanem et al, 2017;Bai et al, 2019;Rohmah et al, 2022) or in chicken (Cui et al, 2006). In chicken, PRL/PstI +/+ genotype was associated with higher egg production at the age of 40 wks (Nagaraja et al, 2000) or at 48 and 57 weeks of age (Li et al, 2008) than PRL/PstI -/genotype have reported similar trend of results on egg production in this current study.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Investigated from five native duck breeds (Shanma, Shaoxing, Jinyun, Jingjiang and Youxian), Wang et al (2011) reported that polymorphism at PRL/PstI in exon 5 was detected, and ducks bearing CC genotype possessed higher egg production as well as egg weight than those of the CT genotype. Similar results of polymorphism at the PRL/ PstI locus in different duck breeds and its relationship with reproductive traits such as egg production ability was also reported in other studies in ducks (Ghanem et al, 2017;Bai et al, 2019;Rohmah et al, 2022) or in chicken (Cui et al, 2006). In chicken, PRL/PstI +/+ genotype was associated with higher egg production at the age of 40 wks (Nagaraja et al, 2000) or at 48 and 57 weeks of age (Li et al, 2008) than PRL/PstI -/genotype have reported similar trend of results on egg production in this current study.…”
Section: Resultssupporting
confidence: 86%
“…pcr aND pcr-rfLp assay A fragment of 536 bp of the PRL gene in exon 5 was successfully amplified in all duck samples and the representative electrophoresis image with the 536 bp fragment was clearly observed in the Figure 2. Similar with current study, many studies have also successfully amplified the target gene on exon 5 of the prolactin gene with various fragment sizes in ducks (Mazurowski et al, 2016;Ghanem et al, 2017;Yurnalis et al, 2019;Purwantini et al, 2020) or in chicken (Rashidi et al, 2012;Mitrofanova et al, 2017;Perdamaian and Daryono, 2020;Rohmah et al, 2022). As shown in Figure 3, polymorphism at the PRL/Pstl with two alleles (C and T) and three genotypes (CC: 536 bp; TT: 406/130 bp and TC: 536/406/130 bp) was clearly distinguished.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In poultry, several candidate genes have been identified showing polymorphism associated with egg production. The prolactin (PRL) gene has important functions in birds, specifically in egg production in chicken (Li et al, 2009;Rowshan et al, 2012;Wilkanowska et al, 2014;Brijendra et al, 2018;Roy et al, 2020;Manoharan et al, 2021;Rohmah et al, 2022), duck (Wang et al, 2011;Chuekwon and Boonlum, 2017;Ghanem et al, 2017;Astuti, 2019;Sabry et al, 2020;Nguyen et al, 2023), goose (Ma et al, 2015;Tang et al, 2021), and quail (Yousefi et al, 2012;Lotfi et al, 2013;Eichie et al, 2016). In chicken, the size of the prolactin gene is 9.536 bp and comprises three parts as (i) three promoters (Kansaku, 2000), (ii) five exons (Ohkubo et al, 1998;Miao et al, 1999;Cui et al, 2004), and (iii) four introns (Dhara and Soller, 1999;Au and Leung, 2002).…”
Section: Introductionmentioning
confidence: 99%